SLEEP DEPRIVATION AND THE GLYMPHATIC SYSTEM: MECHANISMS, CAUSATIVE FACTORS, AND NEUROLOGICAL IMPLICATIONS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Sleep is essential for maintaining brain health and supporting many physiological processes, including memory consolidation and metabolic regulation. Recent research has highlighted the importance of the glymphatic system, a brain-wide clearance pathway responsible for removing metabolic waste from neural tissue. This system allows cerebrospinal fluid (CSF) to circulate through perivascular spaces and exchange with interstitial fluid, helping eliminate toxic substances such as β-amyloid and tau proteins. Evidence suggests that glymphatic activity is significantly enhanced during sleep, particularly during slow-wave sleep, when the exchange between CSF and interstitial fluid increases and waste removal becomes more efficient. Sleep deprivation, however, disrupts these processes. Reduced sleep has been associated with decreased CSF flow, impaired waste clearance, and increased accumulation of neurotoxic proteins. Experimental studies in animals and clinical studies in humans demonstrate that both acute and chronic sleep deprivation can negatively affect glymphatic function and may contribute to the development of neurodegenerative diseases such as Alzheimer’s disease. This review examines the structure and function of the glymphatic system, the role of sleep in regulating brain waste clearance, and the mechanisms through which sleep deprivation impairs these processes. It also discusses current experimental evidence and potential therapeutic strategies aimed at improving sleep and protecting brain health.